The community as the patient in malaria-endemic areas: Preempting drug resistance with multiple first-line therapies. - Boni, M; White, N; Baird, J (Public Library of Science, 2016)
Combination therapy is an effective way to delay or prevent drug-resistance evolution in malaria, but we do not take full advantage of its potential. Deploying multiple first-line combination therapies allows us to challenge parasite populations with many different types of drugs, and thus delay and slow down drugresistance evolution more than with a single combination therapy. We must take a preemptive, not reactive, policy approach to drug-resistance management in malaria.